Initial Experience of Laparoscopic Distal Pancreatic Resections: A Single Institution Study with Fifteen Consecutive Cases - Bakhtiar, Nighat; Shakeel, Osama; Begum, Saleema; Kabir, Syed Irfan; Syed, Aamir Ali (Pakistan Armed Forces Medical Journal, 2023)
Objective: To review the initial experience of outcomes of a consecutive series of laparoscopic distal pancreatic resections are performed at a dedicated cancer hospital.Study Design: Case series.Place and Duration of Study: Department of Surgical Oncology at Tertiary Care Hospital, from Mar 2013 to Feb 2021.Methodology: A retrospective review of consecutive series of patients in which distal laparoscopic pancreatic resections were performed. Data was collected through the Hospital information system (HIS), an electronic hospital database. All patients were discussed in a multidisciplinary team prior to surgery.Results: Fifteen patients, including 4(26.6%) males with a mean age of 49.27±15.2, were planned for laparoscopic distal pancreatectomy. Pathologically, 12(80%) tumours were malignant, while three were benign. The procedure was converted to open in 3 patients. The mean operating time was 4.6±0.57 hours, with an estimated blood loss of around 183±28. 8mls.Mean hospital stay was 5.3±1.5 days. One patient developed a Grade A pancreatic fistula. Recurrence in the liver occurred in two patients, which was managed by systemic adjuvant therapy. However, one of them died later on because of sepsis.Conclusion: A laparoscopic distal pancreatectomy is a safe approach for distal pancreatic tumours, with minimal complications and fast recovery in appropriate cases.